(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
The variability in phosphorus concentrations and the decomposition rates of organic phosphorus were measured in five selected rivers through four surveys in July and November of 2012, and February and May of 2013. After collection the water samples were incubated for 20 days in a dark incubator and the change of forms of phosphorus such as particulate organic phosphorus (POP), dissolved organic phosphorus (DOP) and dissolved inorganic phosphorus (DIP) were analyzed. By fitting the changes to two types of models, the decomposition rates of organic phosphorus were determined. The mean total organic phosphorus (TOP) decomposition rate coefficients in the studied rivers was 0.039 day-1. The average POP decomposition rate coefficient (POP?DOP?DIP model) was 0.038 day-1 while the mean DOP decomposition rate coefficient was 0.251 day-1. The decomposition rate coefficients measured in this study might be applicable for modeling of river water quality. Int. J. Agril. Res. Innov. & Tech. 5 (2): 31-36, December, 2015